State Per Capita Income Components, 1919-1951 - Hanna, Frank A. (The Review of Economics and Statistics, 1956)
STATE income payments are the sums of the streams of wages and salaries, of proprietors' income, of property incomes, and of transfer payments flowing to the states' residents. In highly industrialized states the flow of wages and salaries will be relatively larger than in states more sparsely populated and heavily dependent upon farming. In the latter group of states, the flow of proprietors' income will be relatively larger. To some extent, at least, the recipients of property incomes may choose their place of residence without regard to the location of the property or activity giving rise to the income. rules under which persons receive some of the transfer payments, such as unemployment insurance or workmen's compensation, gear these payments closely to industrial activity. Other transfer payments, such as old-age pensions or veterans' benefits, may be distributed under rules which are largely independent of the type or magnitude of the industrial activity near the recipients' residences; these rules, however, may make qualifying for the transfer payments more attractive in some localities than in others. These component payments vary widely by state. It is the purpose of this paper to examine the interstate variability of the income components and their effects on state differences in per capita incomes. basic data are those provided by the National Division relating to I929, I933, and I939-5i, and by King and Leven for I919-2I.1These data are in terms of the aggregate amounts received by the residents of each state. Two series of adjustments are made to compensate for the large differences in state population. first is to reduce the data to a per capita basis.2 second is to express each component as a percentage of the state's total income payments. latter adjustment, while not explicitly taking state population differences into account, renders the data independent of these differences. Unlike national income, state income payments do not measure the returns to the factors of current productive activity during a specified year. Only those payments actually received by persons are included, and these are included whether they arise from current or from past economic activity. Consequently, these data cannot be used to judge whether there have been shifts in factor returns over the period.3 They do show, however, the changes in the forms in which income is made available to the residents of the various states. Some of these changes may have stemmed from changes in the relative importance of factors, such as the relative productivity of labor and capital; others, however, may simply reflect transitory phenomena, such as a short-lived increase in corporate savings. In the next section the relative interstate dispersion of per capita income is studied as a function of the manner in which the four components combine to form state per capita incomes. This is followed by an examination of the composition of state incomes in terms of their components. Finally, the wages and sal*This report was developed as a part of the Study of Differences in State Per Capita Incomes, which is being financed jointly by Duke University and Rockefeller Foundation. Mrs. Rena B. Webster supervised the basic computations for this report. 'Survey of Current Business, August I953, for I950-5I data; August I952, for I948-49 data; August I950, for I942-47 data; and August I945, for I929, I933, and I9394I data. W. I. King and M. Leven, in the Various States, Its Sources and (National Bureau of Economic Research, New York, I925), provide estimates for I9I9-2I. King-Leven estimates include transfer payments in wages and salaries. State income for I9I9-2I iS taken as the sum of the components and omits certain imputed and in-kind incomes separately estimated by King and Leven. District of Columbia is excluded from this analysis. 2 National Division estimates divided by the most recent Census Bureau estimate of state population as of July i of the relevant year. 'For recent discussion of changes in factor returns, see Jesse Burkhead, Changes in the Functional of Income, Journal of the American Statistical Association, 48 (June I953), I92; Edward F. Dennison, Distribution of National Income, Survey of Current Business (June 1952), i6, and Income Types and the Size Distribution, American Economic Review, Papers and Proceedings, xLiv (May I954), 254; and George J. Schuller, The Secular Trend in by Type, I869-I948: A Preliminary Estimate, this REViEW, xxxv (November I953),